Desafios epistemológicos para a implementação de avaliações institucionais na educação básica - Santos, José Roberto de Souza (2018)
In the face of the growing interest in adopting institutional assessments by networks and teaching systems, as a way of establishing formative evaluation practices, we were interested in this study to understand the challenges and advances in the implementation of this kind of evaluation in one of these networks: the Public Education Network in Distrito Federal, Brazil’s capital. The methodology of the study consisted of bibliographical research, documentary analysis, interviews with the managers of the educational evaluation area of the central bureau of the education system and collective case studies, in which we did observations, documentary analysis, individual interviews and focus groups. The theoretical corpus of work, based on which we built a kind of grammar of the institutional evaluation in basic education, was formed by Freitas (FREITAS, 2005; FREITAS et al., 2009), Sordi (2006, 2009b, 2010, 2011, 2012), Saul (1995), Leite (2005), Dias Sobrinho (1998, 2002, 2003), Nevo (1997, 1998), Cousins (COUSINS; EARL, 1992; CHOUINARD; MILLEY; COUSINS, 2004), Bondioli (2013, 2015) and Chapman and Sammons (2013). In order to approach its implementation in schools and educational networks, we have used Fullan (2009) and studies published in Brazil that address the implementation of this kind of educational change: Sordi (2006, 2010, 2011, 2012), Betini (2010), Mendes and Sordi (2012), Souza and Dittrich (2012), Brandalise (2015), and Mendes et al. (2005), Dalben (2010), Ribeiro and Gusmão (2010), Silva (2010) and Brandalise and Martins (2015). After analyzing the research data, it was observed that the main intervening factor of the implementation of institutional evaluation processes in the schools of the Public Education Network of Distrito Federal is the participation of the community, both as an inspiring aspect of change and as an inhibitor. From the perspective of the central bureau, the most obvious challenge was the use of evaluation results for improvement purposes. The proposition of external evaluations, in turn, with formative function can be highlighted as an important advance. However, since their results were not used in the investigated school units and the relationship of schools with external evaluation initiatives was one of distrust and non-belonging, in addition to the literature, it was inferred that the main reason for this non-use would be the fact that they are non-participatory evaluations. With this, it was possible to conclude that the great challenge of the Public Education Network of the Distrito Federal with a view to the implementation of institutional evaluation processes is the participation, both in schools, and in the relationship of schools with the external entities. Before this scenario, it was pointed out the need for cooperative models of institutional evaluation, in which external bureau and school community cooperate in the evaluation and construction of the quality of schools and the educational network, which involves changes in the relationship of schools with their community and government with school units, currently based on the notion of another as an object, in a subject-subject relationship.